2018
DOI: 10.1038/s41566-018-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

Polarization control of isolated high-harmonic pulses

Abstract: High-harmonic generation driven by femtosecond lasers makes it possible to capture the fastest dynamics in molecules and materials. However, thus far, the shortest isolated attosecond pulses have only been produced with linear polarization, which limits the range of physics that can be explored. Here, we demonstrate robust polarization control of isolated extreme-ultraviolet pulses by exploiting non-collinear high-harmonic generation driven by two counter-rotating few-cycle laser beams. The circularly polarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(73 citation statements)
references
References 50 publications
2
71
0
Order By: Relevance
“…(so e.g. j (13) γ =26 3 and j (14) γ = 28 3 ) and, following the definition of the TKAM, its OAM would be q = j (q) γ − γS q = (2q ± 1)/3 for right-(+) and left-(−) polarized harmonics (therefore giving 13 = 14 = 9, in agreement with the results of Refs. 41, 50).…”
supporting
confidence: 87%
See 2 more Smart Citations
“…(so e.g. j (13) γ =26 3 and j (14) γ = 28 3 ) and, following the definition of the TKAM, its OAM would be q = j (q) γ − γS q = (2q ± 1)/3 for right-(+) and left-(−) polarized harmonics (therefore giving 13 = 14 = 9, in agreement with the results of Refs. 41, 50).…”
supporting
confidence: 87%
“…HHG is a nonperturbative phenomenon which is best understood using a semiclassical picture: an ionized electron is accelerated back to its parent ion, emitting high-frequency light in the ensuing recollision [9][10][11]. Despite the lack of a photonexchange model, HHG is often regarded as a parametric process, and its conservation properties have been explored extensively as regards energy [12], linear momentum [13], and orbital and spin angular momentum (SAM) [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, intensive efforts have been made towards circularly polarized HHG. Use of two counter-rotating circularly polarized laser fields has lead to the breakthrough of circularly polarized high harmonic [3][4][5] and isolated attosceond pulse [6] generation experimentally. Later, it was numerically demonstrated that circularly polarized XUV and attosceond pulses can also be generated via HHG from relativistic plasma surfaces [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…(The same configuration was explored in fact 20 years earlier [128], but the experimental work emphasized the generation, rather than the polarization state, of the emission.) More recently, a number of different methods for generating APTs, as well as isolated attosecond pulses, of circular polarization have been demonstrated [129][130][131][132]. Using tomographic reconstruction in polarization-dependent surface photoemission, the polarization state of these APTs can be reconstructed and compared with theory ( figure 9).…”
Section: (E) Control Of Spectrum and Polarizationmentioning
confidence: 99%